Visitors' Experience at Historical Sites in the City of Amman: A Case Study - Ghaida Irmeili; Ayça Yeşim Çağlayan (Camarines Sur Polytechnic Colleges, 2022)
Historical sites are a deep cultural heritage element that expresses the city's identity and its ancient life. Most cities have a long-civilized history, and the aspects of modern cities rely on it. However, some historical sites remained clear within the components of modern cities, so they became distinctive landmarks and points of attraction for local visitors and tourists, even becoming essential places for recreation and changing the routine of contemporary life. The moving from a historical site to the elements of a modern city needs a deliberate natural planning gradation. The landscape and gardens were the most appropriate for this transition in some places, acting as a natural separator between these two time periods and attractive places for visitors. This research presents the importance and impact of historical and archaeological sites on the inhabitants of the modern city, the behaviors and experiences of visitors as they move from busy city life and modern-day technology to ancient, nostalgic places. And how the parks and surrounding areas of the archaeological site helped integrate modern civil society with the image of the old city. Through a case study in Amman / Jordan, "The Roman Amphitheater and Amman citadel, a special questionnaire was conducted to find out the visitors' opinions, feelings, and behaviors of infamous sites in Amman. As a result of the study and questionnaire and specific questions, the historical sites have a significant emotional, psychological, and even spatial position for visitors to cities. They prefer them to the rest of the town.